Expression of MicroRNAs associated with Gleason grading system in prostate cancer: miR‐182‐5p is a useful marker for high grade prostate cancer. Issue 8 (26th November 2012) - Tsuchiyama, Katsuki; Ito, Hideaki; Taga, Minekatsu; Naganuma, Seiji; Oshinoya, Yukinosuke; Nagano, Ken‐ichi; Yokoyama, Osamu; Itoh, Hiroshi
Abstract: BACKGROUND: Expression profiles of some microRNAs (miRNAs) were associated with clinicopathological findings in human prostate cancer (PC), but the relative expression of miRNAs among Gleason patterns (GPs) remains unclear. In this study, we investigated the expression of several known microRNAs in each GP of PC. METHODS: Formalin‐fixed, paraffin embedded (FFPE) tissue samples were obtained from radical prostatectomy (RP) (patient set 1, n = 43, including (GP 3) n = 22, (GP 4) n = 35, and (GP 5) n = 12) and needle biopsy (patient set 2, n = 10, (GP 4) n = 10). Cancer tissues from each GP and adjacent normal counterparts were separately collected using laser‐captured microdissection (LCM). Real‐time RT‐PCR was performed to determine the relative expression of miRNAs, including miR‐31‐5p, ‐34c‐5p, ‐96‐5p, ‐182‐5p, ‐183‐5p, ‐205‐5p, ‐221‐3p, and ‐222‐3p, which were currently reported to be involved in PC progression. RESULTS: In radical prostatectomy samples, relative expression of miR‐31‐5p, miR‐34c‐5p, and miR‐205‐5p in any GP was significantly decreased compared to normal counterpart. However, no significant difference was detected among GP 3, GP 4, and GP 5. Meanwhile, in the same GP4, expression of miR‐31‐5p miR‐182‐5p, and miR‐205‐5p in cancer tissues obtained from high grade cancer was significantly higher than those obtained from intermediate grade cancer. Validation study using biopsy samples revealed that the relative expression of miR‐182‐5p was statistically higher in high grade cancer even in same GP4. CONCLUSIONS: We confirmed the expression of miR‐182‐5p depended on the cancer grade even in same GP 4. Expression of miRNA associated with Gleason grading system may contribute to more accurate preoperative cancer risk evaluation. Prostate 73: 827–834, 2013. © 2012 Wiley Periodicals, Inc.